Good news and bad news in subjective performance evaluation - Jörg Budde (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Earlier studies show that contracts under subjective performance evaluation are dichotomous and punish only worst performance. I show that with limited liability payments need not be binary. More importantly, if the agent earns a rent from limited liability, the optimal contract distinguishes only signals of good news and bad news of the agent's action.
urn:nbn:de:bvb:19-epub-17411-3
Keywords: D82; M52; M54; 330; bonus; monotone likelihood ratio; wage compression